O professor de português língua estrangeira como interculturalista em contexto de extensão universitária - Jesus, Isabela Abê de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This investigation handles the teacher as an interculturalist in a multicultural context of teaching and learning Portuguese as a Foreign Language (PFL) (ALMEIDA FILHO, 2001, 2004, 2007, 2009; CUNHA, 2007; KFOURI-KANEOYA, 2008, 2013, 2015; SERRANI, 2005; MENDES, 2003, 2004a, 2011). The study aimed at investigating how the participant teacher explores the intercultural aspects that permeate the learning and teaching process of PFL; and observe the contributions of the interculturality in this context to the education of PFL teacher as an interculturalist (SERRANI, 2005). Two questions and a sub question were proposed. The first research question had the purpose of analyzing how the participant teacher explores interculturalism in class, and the sub question related to it had the intention to discuss the conceptions of culture revealed in the teacher's sayings and doings; by its turn the second research question had as its objective to discuss how interculturalism present in the investigated context can contribute to the education of PFL teacher as an interculturalist. The research study has two focuses: the first are the teaching practices of a teacher in a class of a regular course of PFL at UNESP (São José do Rio Preto), at the level of beginners, in which the learners are undergraduate and post-graduate students in a situation of academic immersion, coming from partner foreign universities of the Brazilian institution; the second focus is on the participation of the same teacher in the weekly meetings of the education, research and teaching group of the extension project in which the regular course is inserted. According to a qualitative study of ethnographic nature (ANDRÉ, 2000; RICHARDS, 2003) and with characteristics of collaborative research, the data were generated through (i) audio recordings of PFL lessons taught by the participant teacher; (ii) audio recordings of the meetings of the formation, research and teaching ...

Esta investigação trata do professor como interculturalista em um contexto multicultural de ensino e aprendizagem de Português Língua Estrangeira (PLE) (ALMEIDA FILHO, 2001, 2004, 2007, 2009; CUNHA, 2007; KFOURI-KANEOYA, 2008, 2013, 2015; SERRANI, 2005; MENDES, 2003, 2004a, 2011). Este estudo teve como objetivos investigar o modo como a professora participante explora os aspectos interculturais que permeiam o processo de ensino e aprendizagem de PLE no contexto da pesquisa; e observar as contribuições da interculturalidade presente nesse contexto para a formação do professor de PLE como interculturalista (SERRANI, 2005). Foram propostas duas perguntas e uma subpergunta de pesquisa. A primeira teve como propósito analisar o modo como a professora participante explora a interculturalidade em sala de aula, e a subpergunta relacionada a ela teve por intuito discutir as concepções de cultura reveladas no dizer e fazer da professora; a segunda pergunta de pesquisa, por sua vez, teve como objetivo discutir de que modo a interculturalidade presente no contexto investigado pode contribuir para a formação do professor de PLE como interculturalista. A pesquisa se realizou em um contexto de ensino e aprendizagem de PLE, contemplando dois focos: o primeiro são as práticas docentes de uma professora em sala de aula de curso regular de PLE na UNESP de São José do Rio Preto, em nível iniciante, cujo público são alunos de graduação e de pós-graduação em situação de imersão acadêmica, provenientes de universidades estrangeiras parceiras da universidade brasileira; o segundo foco são as participações da mesma professora nas reuniões semanais da equipe de ensino, pesquisa e formação do projeto de extensão no qual o curso regular está inserido. De acordo com um estudo qualitativo de cunho etnográfico (ANDRÉ, 2000; RICHARDS, 2003) e com características de pesquisa colaborativa, os dados foram gerados por meio de (i)...
Keywords: Linguistica aplicada; Lingua portuguesa - Estudo e ensino - Falantes estrangeiros; Professores de português - Formação; Linguagem e cultura; Professores universitários; Applied linguistics